Gangguan Berbahasa Tokoh Dodo Rozak pada Film Miracle in Cell No. 7 Versi Remake Indonesia Kajian Psikolinguistik: Language Disorder of the Character Dodo Rozak in the Film Miracle in Cell No. 7 Indonesian Remake Versions Psycholinguistic Studies - Purnama, Ahmad Ri'i Nanda; Kinanti, Kingkin Puput (Universitas Nusantara PGRI Kediri, 2024)
This research delves into the language disorders portrayed by Dodo Rozak in the Indonesian film